Women’s Attitude for a Male Offspring and Related Family Planning Practices - Rasheed, Nazish; Khan, Zulfia; Khalique, Najam; Pathak, Rambha (National Journal of Community Medicine, 2017)
Background: Son preference in India is widespread and deep rooted. Parents’ expectations of benefits and costs are biased in favour of sons. This therefore acts as the key motivation for the preference of male offspring. Women might continue to bear children until the desired number of sons is reached. Methodology: A community based, cross-sectional study was carried out among 718 married women of reproductive age group selected by systematic random sampling. Results: The present study revealed that 63.1% women were of the opinion that it was necessary to have a male child. Women were more likely to be acceptors of contraception even if they had one son (38.8%) as compared to women having no sons (17.9%) and the relationship was found to be significantly associated. Women who accepted terminal method of contraception over spacing method was significantly higher among women having male offspring. Conclusions: The findings demonstrate that in settings like Uttar Pradesh, focusing solely on family-size limitation may not be an effective strategy to promote family planning because it is women’s preference for sons – and not just family size – that plays a key role in determining if, when and how a woman regulates her fertility.